Guidelines for the Conservation of Local Knowledge on Silk Weaving in Phanom Village, Luang Prabang Capital, Luang Prabang Province - invankham, maiphone; phaignavong, somchay; soulivong, phetsamone; keopaseuth, dalyvone (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study used a qualitative method through inherited weaving to reserve for generation to generation. The purposes of this study were to study: 1) the local knowledge about the silk weaving of women in Phanom Village; 2) the way to preserve the local knowledge of silk weaving of women in Phanom Village, Luang Prabang. The target group was 30 participants, using document analysis, related studies, focus group interviews, and direct interviews with silk producers. Data analysis was implemented with a descriptive method to lead to a causal explanation of the data. The results showed that 1) The inheritance of local knowledge in silk weaving by women in Ban Phanom, Luang Prabang City, Luang Prabang Province. First, it is inherited from mothers, secondly, it is inherited from relatives, and then it is inherited from friends and society and 2) The guidelines for the conservation of silk weaving were organized through the operation process as follows: (1) The target group was defined by the weaving group, the head of the weaving center, and the village chief; (2) determined the pattern of transferring knowledge by continuous operation; (3) the ancestors had to be individuals in the target community, who were knowledgeable and accepted by the members of the village; (4) those who inherited weaving had to be interested and highly motivated; (5) the place to transfer knowledge was the area of the center and each person’s house; (6) The transmission process was divided into two periods: the actual study period and the performance monitoring period; (7) the method of transmission was the nature of practical training, while the atmosphere was carried out independently and (8) the assessment was based on the standards of the transmitters, the production center, and the markets.